Surgical management of familial pancreatic cancer: a systematic review of the literature. Issue 11 (27th June 2022) - Bagias, George; Kanavidis, Prodromos; Vailas, Michail; Despotidis, Markos; Sotiropoulou, Maria; Katsaros, Ioannis; Maroulis, Ioannis; Filippou, Dimitrios; Schizas, Dimitrios
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is the third most common cause of cancer‐related mortality. The fact that the vast majority of patients with PDAC are diagnosed at an advanced stage highlights the need of early diagnosis. As hereditary factors are associated with approximately 5% of all PDAC cases, a screening programme to these high‐risk individuals (HRI) has been proposed. The aim of screening methods is to identify selected group of patients with morphological abnormalities at an early stage, in order to be treated promptly. In this study, we evaluate the surgical outcomes and the appropriateness of pancreatic resection in HRIs who were selected for screening. Methods: A systematic literature search of the PubMed, Embase, and Cochrane databases was performed. The clinicopathological features were recorded and evaluated. Results: Six studies were selected for data collection. A total number of 77 patients were identified. Twenty‐one patients had a germline mutation, with CDKN2A being the most prominent one (15.6%). Distal pancreatectomy was the most common surgical procedure (42.8%), followed by pancreaticoduodenectomy (33.8%). The mean disease‐free survival was 23.6 months and tumour recurrence occurred in 9 patients (11.7%). Disease‐specific mortality was 17.8%, while overall mortality was 19.5%. The most frequently reported postoperative diagnosis was PDAC (28 cases, 38.9%), followed by IPMN (23 cases, 31.9%), whereas high‐grade PanIN lesions were found in 13 patients (18.1%). Conclusion: High‐risk individuals for pancreatic cancer, who are eventually operated may have a relatively uneventful postoperative course, however the oncological outcomes are comparable to the general population. Abstract : High‐risk individuals for pancreatic cancer, who are eventually operated may have a relatively uneventful postoperative course, however the oncological outcomes are comparable to the general population.